The mathematical approach for proximity analysis for 3D GIS - Chen, Tet Khuan (Penerbit UTM, 2008)
Next generation of GIS software would highly depend on 3D analysis in solving geographic problems. 3D analysis is a very important component for GIS as it defines as decision making tools for geographic features. One would like to query about geographic object from numerical calculation or propose optimum solutions for GIS applications. Such desired components in future software or system are to deal with the 3D analytical solutions. This paper presents a portion of the problems, which are 3D solid buffering for 3D GIS. This analytical solution is very important for 3D spatial analysis. The discussion related to the implementation of buffering model for solid object is the main concern in the research, where the primitive objects of point, line, and face will be taken in consideration for the development of 3D solid buffering